INTERNALISASI NILAI AKHLAKUL KARIMAH DALAM MEMBENTUK ETIKA SISWA - Ahmat Rifa’i; Hilmiati Hilmiati; M. Sobry; Maimun Maimun; Mira Mareta (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study was motivated by the importance of developing students’ ethics through the internalization of akhlakul karimah values in the school environment. The study aimed to analyze the process of internalizing akhlakul karimah values in shaping students’ ethics at SMPN 4 Janapria. This research employed a qualitative approach with a case study design. The research subjects consisted of Islamic Education teachers, students, and school authorities selected through purposive sampling techniques. Data were collected through observation, interviews, and documentation, then analyzed using interactive analysis techniques involving data reduction, data presentation, and conclusion drawing. The results showed that the internalization of akhlakul karimah values was carried out through three stages, namely value transformation, value transaction, and transinternalization. The process was implemented through Islamic Religious Education learning, teacher role modeling, habituation, school culture, and religious activities such as congregational prayers, short religious lectures (kultum), Qur’an recitation, and the 5S program (smile, greeting, salutation, politeness, and courtesy). In addition, the concepts of sam’ and fu’ad from the perspective of Islamic psychology indicate that value internalization not only affects cognitive aspects but also students’ spiritual and psychological dimensions. Therefore, the internalization of akhlakul karimah values plays an important role in shaping students’ ethics through the integration of learning, school culture, and continuous religious habituation. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya pembentukan etika siswa melalui internalisasi nilai akhlakul karimah di lingkungan sekolah. Penelitian ini bertujuan untuk menganalisis proses internalisasi nilai akhlakul karimah dalam membentuk etika siswa di SMPN 4 Janapria. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian terdiri atas guru Pendidikan Agama Islam, siswa, dan pihak sekolah yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan teknik analisis interaktif melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa internalisasi nilai akhlakul karimah dilakukan melalui tiga tahapan, yaitu transformasi nilai, transaksi nilai, dan transinternalisasi. Proses tersebut dilaksanakan melalui pembelajaran Pendidikan Agama Islam, keteladanan guru, pembiasaan, budaya sekolah, serta kegiatan keagamaan seperti shalat berjamaah, kultum, membaca Al-Qur’an, dan program 5S (senyum, salam, sapa, sopan, santun). Selain itu, konsep sam’ dan fu’ad dalam perspektif psikologi Islam menunjukkan bahwa internalisasi nilai tidak hanya menyentuh aspek kognitif, tetapi juga aspek spiritual dan psikologis peserta didik. Dengan demikian, internalisasi nilai akhlakul karimah berperan penting dalam membentuk etika siswa melalui integrasi pembelajaran, budaya sekolah, dan pembiasaan religius secara berkelanjutan.